2018
DOI: 10.14710/jtsiskom.6.4.2018.152-157
|View full text |Cite
|
Sign up to set email alerts
|

Paralel Spatial Pyramid Convolutional Neural Network untuk Verifikasi Kekerabatan berbasis Citra Wajah

Abstract: In this paper, we proposed a parallel spatial pyramid CNN classifier for image-based kinship verification problem. Two face images that compared for kinship verification treated as input for each parallel convolutional network of our classifier. Each parallel convolutional network constructed using spatial pyramid CNN classifier. At the end of the convolutional network, we use three fully connected layers to combine each spatial pyramid CNN features and decided the final kinship prediction. We tested the propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
4
0
4
Order By: Relevance
“…Analisis dan pemodelan citra wajah merupakan bidang riset yang aktif dalam era big data saat ini. Beragam metode telah digunakan dalam penelitian citra wajah, di antaranya metode klasifier parallel spatial pyramid Convolutional Neural Network (CNN) untuk verifikasi kekerabatan berbasis citra wajah [4] dan identifikasi citra wajah dengan Hidden Markov Model (HMM) [5]. Aplikasi pengenalan citra sketsa wajah manusia juga telah dikembangkan dengan beberapa metode lain, di antaranya Structure Co-occurrence Texture (SCOOT) untuk evaluasi struktur spasial dan ko-okurensi tekstur [6], klasifier Bayesian [1], dan Eigenface [7].…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Analisis dan pemodelan citra wajah merupakan bidang riset yang aktif dalam era big data saat ini. Beragam metode telah digunakan dalam penelitian citra wajah, di antaranya metode klasifier parallel spatial pyramid Convolutional Neural Network (CNN) untuk verifikasi kekerabatan berbasis citra wajah [4] dan identifikasi citra wajah dengan Hidden Markov Model (HMM) [5]. Aplikasi pengenalan citra sketsa wajah manusia juga telah dikembangkan dengan beberapa metode lain, di antaranya Structure Co-occurrence Texture (SCOOT) untuk evaluasi struktur spasial dan ko-okurensi tekstur [6], klasifier Bayesian [1], dan Eigenface [7].…”
Section: Pendahuluanunclassified
“…Di sisi lain, sketsa yang dilukis dengan pensil di atas kertas (viewed sketches) memiliki tekstur yang berbeda dibandingkan dengan kulit manusia yang diambil pada foto, terlebih dengan adanya tekstur bayangan untuk menyampaikan informasi bayangan 3D [7]. Berbeda dengan [1], [4]- [9] yang menggunakan data citra foto sebagai masukan, penelitian ini mengkaji aplikasi pengenalan wajah menggunakan dokumen hasil sketsa wajah (viewed sketches) sebagai masukan sistem dan dibandingkan dengan basis data foto wajah. Berbeda dengan [10] yang menggunakan LFDA, ekstraksi ciri dari sketsa dan foto wajah dalam kajian ini dilakukan dengan metode PCA.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Apart from these traditional methods, deep learning-based approaches lately achieved state-of-the-art performance in kinship verification. Widely used architectures, e.g., VGG16 [9], GAN & ResNet [10], SphereFace [11], SPCNN [12], ShallowResNet [13] and VGGFace [14]- [16] have been used for this task. Laiadi et.…”
Section: Related Workmentioning
confidence: 99%
“…For instance, studies on ripeness estimation of grapes [22], banana [23], pineapple [24], durian [25], coffee beans [26], and other artificially ripened fruits [27] have utilized the potential of CNN in carrying out high accuracy classification. Other useful studies on the manipulation of CNN modeling are shown in other applications like in [28]- [30], while commonly used machine learning like SVM, Decision Tree, and Naïve Bayes can also be used in training the data [31], [32].…”
Section: Introductionmentioning
confidence: 99%